Pengembangan Potensi IKM Kreatif Berbasis Teknologi di Kabupaten Mojokerto - Fitra Ria Silvida; Luki Ardiantoro; Meila Sari; Aulia Zanuarisma (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Creative small and medium industries (SMEs) have an important role in regional economic growth, including in Mojokerto Regency. However, challenges such as limited access to technology, digital marketing, and product innovation are still major obstacles to the development of creative SMEs. This study aims to identify the potential of creative SMEs in Mojokerto Regency and develop technology-based strategies to improve their sustainable competitiveness. The research method used is a qualitative approach through surveys and interviews. The results of the study show that the use of technology in digital marketing production, and business management contributes significantly to increasing the efficiency and market reach of Creative SMEs. Thus, the development of technology-based creative SME potential is expected to be a strategic solution in encouraging regional economic growth and improving the welfare of SME business actors in Mojokerto Regency.